P1468ASSESSING THE BURDEN OF CHRONIC PAIN IN PATIENTS UNDERGOING HAEMODIALYSIS: A CROSS-SECTIONAL OBSERVATIONAL STUDY. (6th June 2020) - Bell, Samira; Lambourg, Emilie; Guthrie, Greg; Murugan, Krithi; Colvin, Lesley; Traynor, Jamie P
Abstract: Background and Aims: Chronic pain is a global health problem estimated to affect between 20- 50% of the population and is associated with increased hospitalisations placing a significant burden on healthcare resources. The burden of chronic pain is thought to be especially high in patients undergoing renal replacement due to underlying co-morbidities such as diabetes, peripheral vascular disease and renal bone disease. There is, however, a lack of data out with the United States quantifying the burden in patients undergoing chronic dialysis. The aim of this study was to establish the burden of chronic pain through examination of prescribing records in patients undergoing chronic dialysis. Method: We performed a cross sectional observational study in 2 Scottish health boards (together serving 1.9 of Scotland's 5 million population). Data were collated on age, dialysis vintage, primary renal diagnosis and analgesia prescribing specifically examining whether patients were prescribed paracetamol, non-steroidal anti-inflammatory agents, opioids or gabapentinoids. Descriptive statistics were performed. Results: 721 patients receiving haemodialysis were included in the analysis (141 from the Tayside area and 580 from Greater Glasgow and Clyde). Mean age was 64 years old (SD 14.4) with a median time since commencing renal replacement therapy of 3 years (IQR 1.4-6.4). The primary renal diagnosis was diabetes for 28% of the patients, multisystem diseases for 21.6%, interstitial nephropathies for 21.5%, primary glomerulonephritis for 15.8%, and unknown or related to another disease for 10%. Of these 527 (73%) were prescribed a form of analgesia. 404 patients (56%) were prescribed paracetamol, 14 (1.9%) were prescribed a non-steroidal anti-inflammatory, 96 (35.4%) an opioid, 71 (9.8%) a combination of paracetamol with opioid, 170 (23.6%) a gabapentinoid and 100 (14%) were prescribed both a gabapentinoid and opioid. There was no difference in age between those receiving analgesia and those who were not (63.5 vs 65.2, p=0.13). However patients receiving opioids were significantly younger than those who were not prescribed any opioid (62.2 SD 13.9 vs 65 SD 14.5, p-value = 0.001; Wilcoxon rank sum test). There was no difference in percentage of patients receiving analgesia by primary renal diagnosis: Figure 1 (Chi-square test, p=0.1). Conclusion: Prescribing rates of analgesia are high in patients undergoing chronic dialysis suggesting a high burden of chronic pain. Number of patients receiving analgesia (in red) or not (in blue), depending on their primary renal diagnosis. 1=primary glomerulonephritis, 2=interstitial nephropathies, 3=multisystem diseases, 4=diabetic nephropathy, 5=not known or other